An Exploration of Students’ Experiences Using Cake at SMPN 1 Telaga Biru to Enrich Vocabulary - Fadlun Panggi; Titien Fatmawaty Mohammad; Sri Rumiyatining Luwiti (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study explores the experiences of eighth-grade students at SMPN 1 Telaga Biru in using the Cake application to enrich their English vocabulary. Qualitative research design was employed, involving 10 Grade 8 students selected purposively based on their vocabulary levels, experience using the Cake application, and willingness to participate in in-depth interviews. Data was collected through semi-structured interviews and analyzed using thematic analysis. The findings indicate that 8 of the 10 participants perceived the audiovisual features, including videos, subtitles, pronunciation practice, and interactive exercises, as making vocabulary learning more enjoyable. Seven participants considered the application easy to use, while four explicitly reported perceived gradual improvement in their vocabulary. Students also highlighted contextualized conversations and repeated exposure as helpful for understanding and remembering vocabulary. However, three participants reported unstable internet connections, while other challenges included difficulty understanding fast speech, inconsistent learning habits, and distracting learning environments. Overall, the findings suggest that Cake can serve as a useful supplementary medium for contextual and flexible vocabulary learning. However, its effectiveness depends on supporting conditions such as teacher guidance, internet access, and students’ self-regulation.